The Effect of Sundanese Instrumental Music Therapy and The Provision of Spicy Drinks on Pain Intensity and Labor Duration - Ni Gusti Made Ayu Agung Budhi; Ni Nyoman Sasnitiari (Journal of Midwifery, 2021)
The pain in labor due to contractions and the process of expelling the baby cannot be avoided by the mother. One way to reduce pain intensity non-pharmacologically is music therapy and the provision of spice drinks. music therapy can reduce stress and anxiety levels, especially during childbirth, while herbal drinks derived from ginger are analgesic, as well as cinnamon and cloves, can relieve pain. The research method is “Quasi experimental pre-post test with control group design. The intervention group was Sundanese instrumental music therapy with spice drinks and the control group was only given spice drinks, which was carried out on mothers giving birth during an active phase. The population is all mothers giving birth in BPM Bogor area. The sample size of the average difference test of two paired groups is 15 respondents in each group. The results showed a decrease in labor pain in the active phase of the first stage in the intervention group with p = 0.016. This shows that there is an effect of giving music therapy and spice drinks on the intensity of labor pain as assessed by the Visual Analog Scale (VAS), and there is no significant change in the decrease in labor pain during the active phase of labor, in the control group (p>0.05). There was no significant result on the length of labor with p = 0.439 (p > 0.05). This means that both the control and intervention groups did not show a difference in the time/length of labor